2022
DOI: 10.3390/fluids7030094
|View full text |Cite
|
Sign up to set email alerts
|

Computational Methods for Fluid-Structure Interaction Simulation of Heart Valves in Patient-Specific Left Heart Anatomies

Abstract: Given the complexity of human left heart anatomy and valvular structures, the fluid–structure interaction (FSI) simulation of native and prosthetic valves poses a significant challenge for numerical methods. In this review, recent numerical advancements for both fluid and structural solvers for heart valves in patient-specific left hearts are systematically considered, emphasizing the numerical treatments of blood flow and valve surfaces, which are the most critical aspects for accurate simulations. Numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 150 publications
0
2
0
Order By: Relevance
“…Modeling and evaluation of aortic valves performance has been developed by several authors using FSI [62][63][64][65][66][67] while studying the effect of valve shape and geometry on its performance, considering the large deformation of valve leaflets, as well as particular flow characteristics. 39,68 Is has been shown that altering specific angles of a structured stent can significantly lower peak stress on the leaflets, for instance. 66 With the numerical model that our team developed, we could not only find the optimal leaflet thickness, but also the most suitable valve design, reducing stress/strain on the leaflets.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling and evaluation of aortic valves performance has been developed by several authors using FSI [62][63][64][65][66][67] while studying the effect of valve shape and geometry on its performance, considering the large deformation of valve leaflets, as well as particular flow characteristics. 39,68 Is has been shown that altering specific angles of a structured stent can significantly lower peak stress on the leaflets, for instance. 66 With the numerical model that our team developed, we could not only find the optimal leaflet thickness, but also the most suitable valve design, reducing stress/strain on the leaflets.…”
Section: Discussionmentioning
confidence: 99%
“…FSI (fluid-structure interaction) simulation of the aortic valve is a computational technique that combines computational fluid dynamics (CFD) and structural mechanics to analyze the behavior of the aortic valve under fluid flow conditions [155,195,196]. FSI and CFD applications are widely used in biomedical engineering [121,[197][198][199][200].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy to mention that Newtonian behavior has been used to model the blood, which is adequate for shear rates >100 s −1 [46,47]. The fluid-structure interaction (FSI) has received significant attention in research related to cardiovascular modeling [48][49][50][51][52][53][54][55]. In this study, FSI only pertains to the convective heat-sink (cooling) effect induced by the blood flow during cardiac ablation, as the cardiac tissue has been modeled as a rigid body.…”
Section: Methodsmentioning
confidence: 99%